Modernization and the Working Class The Politics of Legitimacy - Waisman, Carlos H. (University of Texas Press, 2021)
This is a fascinating inquiry into the factors that determine the acceptance or rejection of capitalism by the industrial working class. Combining classical social theory, historical evidence, and survey data, Waisman explores the relationship between the degree of modernization and the legitimacy of the capitalist social order. Propositions about the interaction between established elites and emerging working classes are illustrated with three typical cases: Disraelian Britain, Bismarckian Germany, and Peronist Argentina. From the contrasting theories of Marx and Bakunin, the author derives hypotheses concerning the position of the working class in the economy and the consequences this has for legitimacy. He finds that countries at middle levels of industrial development-mostly latecomers to industrialization in Southern Europe and advanced areas of Latin America-have the greatest difficulty in establishing capitalism as a legitimate social order. They are advanced enough to have a large working class, yet underdeveloped enough to have a dissatisfied one